Attitude of clinical teachers towards the use of innovative technology in teaching and learning in the university of Port Harcourt medical school, South Nigeria - Wananyo, Ugboma Enighe; Ebi, Awotua-Efebo; Ibi, Erekosima (Asian Journal of Education and Training, 2024)
The 21st century has seen a rapid increase in the use of various innovative technologies in pedagogy. The attitude of the clinical teachers affects the use of these innovative technologies in teaching and learning. The aim of this research is to find out the attitude of clinical teachers using “The Tripartite Theory of Attitude” consisting of affective, cognitive, and behavioral domains, to the use of innovative technology. A descriptive survey research design with correlational studies was done with a purposive sampling method used. A 24 item Likert questionnaire was used and distributed using Google Form. The population of the study was made up of clinical teachers in the Faculty of Clinical Sciences University of Port Harcourt. A total of 90 clinical teachers took part in the study comprising of 48 males and 42 females. 23 were professors while 51 were senior lecturers. Analysis showed the overall attitude of clinical teachers to the use of innovative technology in teaching and learning was positive. No significant correlation was seen between gender, cadre, and years of service of the clinical teacher to the use of innovative technology. Thus, incorporation of innovative technology into the classroom should be encouraged as this would aid the clinical teachers in improving learning in the classroom.